Meconium stained amniotic fluid and its effect on the early maternal and neonatal outcomes - Sekele, Relebogile (My University, 2020)
Background The presence of meconium during delivery is a common finding and may be associated with significant neonatal and maternal outcomes. Objectives To determine the incidence of meconium stained amniotic fluid (MSAF) at Chris Hani Baragwanath Academic Hospital. To describe the characteristics of women with MSAF and to determine the maternal and fetal outcomes. Methodology A secondary data analysis of the women and neonates exposed to MSAF born between July 2014 and December 2016. We used data that was collected for the V98_28OBTP study, which aimed to establish a sero-correlate of protection, based on maternal and newborn levels of Group B streptococcus anti-capsular antibody and the risk to developing serotype specific invasive Group B streptococcus disease in the newborn. Only singleton deliveries of birthweight ≥1000g and cephalic presentation were included in this study. Exclusion criteria included presence of congenital abnormalities and stillbirths. A comparison was made in women whose neonates had a normal outcome vs. those with severe fetal outcomes. Results Among the 37,725 deliveries, 4218 (11.18%) had meconium stained amniotic fluid (MSAF). Delivery was by caesarean section in 2628 (62.30%) women and 2343 (89.16%) of these were emergency caesarean sections. Of the 1590 vaginal deliveries, 71 (4.47%) were assisted deliveries. Chorioamnionitis was noted in 20(0.47%) women. V Most of the women were black (98.15%), with a mean age of 27.35 and a mean body mass index (BMI) of 29.98. There were 3835(90.92%) term deliveries, with the mean birthweight of 3151g (SD±503.81). The median Apgar score at 5 minutes was 10 (IQR 7-10, range 0-10). There were 232(5.50%) neonates that required resuscitation after delivery. There were 380(9.03%) neonates that were born preterm. The median gestational age of those born preterm was 35 weeks (IQR 29-36; range 25-36). In the comparison of neonates with good outcomes vs. those with severe neonatal outcomes, neonates of the women with offensive amniotic fluid were more likely to have severe neonatal outcomes (P=0.00). Conclusion The incidence of meconium stained amniotic fluid (MSAF) is 11.18%. The incidence of preterm deliveries is 9.03%. The presence of MSAF is associated with a high caesarean rate of 62.30%. The presence of offensive amniotic fluid is associated with severe neonatal outcomes. Women with MSAF should therefore be referred to a centre where caesarean sections and intensive neonatal care are provided.
A dissertation submitted in fulfilment of the requirements for the degree of Master of Science in Medicine in Obstetrics and Gynaecology to the Faculty of Health Sciences, School of Clinical Medicine, University of the Witwatersrand, Johannesburg, 2020